Serum biochemistry, hematology, and reproductive behavior of free-roaming cats in urban and rural habitats. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: A cross-sectional study was conducted to reveal the hematology, serum biochemistry, and reproductive behavior of free-roaming cats in the Sylhet Division of Bangladesh. Materials and Methods: Overall, 130 free-roaming cats were captured, of which 52 were Tom (male), 69 were Queen (female), and 9 were kittens. Regarding their ages, the cats were divided into three groups: